Seasonal and Inter-Annual Variations of Stable Isotopic Characteristics of Rainfall and Cave Water in Shennong Cave, Southeast China, and Its Paleoclimatic Implication - Tian, Ye; Zhang, Haiwei; Zhang, Rui; Zhang, Fan; Liang, Zeyuan; Cai, Yanjun; Cheng, Hai (Frontiers in Earth Science, 2021)
Speleothem calcite stable oxygen isotope (δ18OC) is one of the most widely used proxies in paleoclimate research, and understanding its seasonal-annual variability is very significant for palaeoclimate reconstruction. A five-year precipitation and karst cave water from 2016 to 2021 were monitored in Shennong cave, Jiangxi Province, Southeast China. The local meteoric water line (LMWL) is δD= 8.20×δ18O + 13.34, which is similar to the global meteoric water line. The stable hydrogen and oxygen isotope (δD and δ18O) characteristics of precipitation and cave water were studied. δ18O and δD of precipitation and cave water show obvious seasonal variations. Lower precipitation δ18O and δD generally occur during summer and autumn compared with higher δ18O and δD values during winter and spring. Meanwhile, low precipitation δ18O values do not only appear in June-July when precipitation is the highest of the year but also appear in August-September when precipitation is limited. The back-trajectory analysis of monsoon precipitation moisture sources shows that the moisture uptake regions vary little on inter-annual scales, the water vapor of rainfall in June-July comes from the South China Sea and the Bay of Bengal, while the moisture source in August-September is mainly from the West Pacific and local area. The El Niño-Southern Oscillation is an important factor affecting the value of δ18O by modulating the percentage of summer monsoon precipitation in the annual precipitation and moisture source. The relationship between amount-weighted monthly mean precipitation δ18O and Niño-3.4 index shows that East Asian summer monsoon (EASM) intensifies during La Niña phases, resulting in more precipitation in monsoon season (May to September, MJJAS) and lower δ18O values, and vice versa during El Niño phases.